1267. Five-Year Trend on the Susceptibility of Enterobacterales to Plazomicin and Other Aminoglycosides in Hospitals in the United States (2016–2020). (4th December 2021) - Sader, Helio S; Duncan, Leonard R; Yee, Cheung; Das, Sandhya; Gogtay, Jaideep; Castanheira, Mariana; Castanheira, Mariana
Abstract: Background: Plazomicin (PLZ) is novel aminoglycoside (AMG) that was approved by the US FDA in June 2018 to treat complicated urinary tract infection (cUTI), including pyelonephritis. This agent is active against most isolates resistant to other AMGs. We evaluated PLZ activity against clinical isolates of Enterobacterales (ENT) from US hospitals. Methods: 10, 008 ENT isolates (1/patient) were collected from 35 US medical centers in 2016-2020 and susceptibility tested by the broth microdilution method at a central laboratory. PLZ breakpoints of ≤2/≥8 mg/L for susceptible [S]/resistant [R] (USFDA) were applied, and breakpoints established by the USFDA/CLSI, EUCAST and USCAST were applied to other AMGs for comparison. Isolates were mainly from cUTI (37.7%), bloodstream infection (24.9%), and pneumonia (20.3%). Results: PLZ exhibited potent activity against ENT (MIC50/90, 0.5/1 mg/L), with S rates varying from 97.8% in 2016 to 95.8% in 2020 (96.8% overall). Against carbapenem-R ENT (CRE), S rates for PZL increased from 96.3% in 2016 to 100.0% in 2020 (Figure; 97.3% overall) and were markedly higher than amikacin (AMK; 75.2% overall), gentamicin (GEN; 48.7%), and tobramycin (TOB; 23.0%). The discrepancies between S rates for PLZ and other AMGs were greater when applying breakpoints generated using the same stringent contemporary methods applied to determine PLZ breakpoints. CRE S rates for AMK were 62.8% as per EUCAST and 52.2% as per USCAST. PLZ retained activity against GEN-non-S (NS; n=875; 90.6%S), TOB-NS (n=944; 92.7%S), and AMK-NS (n=60; 83.3%S) isolates. Among isolates from cUTI (n=3, 774), 96.9% were PLZ-S, varying from 97.8% in 2017 to 95.8% in 2020. The ENT species most S to PLZ (lowest MIC values) were C. koseri (100.0%S), K. aerogenes (100.0%S), K. pneumoniae (99.8%S), and E. cloacae (99.7%S), which had MIC50/90 values of 0.25/0.5 mg/L, followed by K. oxytoca (MIC50/90, 0.5/0.5 mg/L; 99.9%S), E. coli (MIC50/90, 0.5/1 mg/L; 99.6%S), and C. freundii (MIC50/90, 0.5/1 mg/L; 100.0%S). Conclusion: PLZ demonstrated potent activity against a large collection of contemporary ENT isolates from US hospitals with 4-fold lower MIC values than AMK. PLZ was markedly more active than AMK, GEN, or TOB against CRE and retained good activity against isolates NS to these AMGs. Disclosures: Helio S. Sader, MD, PhD, FIDSA, AbbVie (formerly Allergan ) (Research Grant or Support)Basilea Pharmaceutica International, Ltd. (Research Grant or Support)Cipla Therapeutics (Research Grant or Support)Cipla USA Inc. (Research Grant or Support)Department of Health and Human Services (Research Grant or Support, Contract no. HHSO100201600002C)Melinta Therapeutics, LLC (Research Grant or Support)Nabriva Therapeutics (Research Grant or Support)Pfizer, Inc. (Research Grant or Support)Shionogi (Research Grant or Support)Spero Therapeutics (Research Grant or Support) Leonard R. Duncan, PhD, AbbVie (formerly Allergan ) (Research Grant or Support)Basilea Pharmaceutica International, Ltd. (Research Grant or Support)Cipla Therapeutics (Research Grant or Support)Cipla USA Inc. (Research Grant or Support)Department of Health and Human Services (Research Grant or Support, Contract no. HHSO100201600002C)Shionogi (Research Grant or Support) Cheung Yee, MSc, PhD, Cipla Therapeutics (Employee) Sandhya Das, n/a, Cipla Therapeutics (Employee) Jaideep Gogtay, n/a, Cipla Therapeutics (Employee)Cipla USA Inc. (Employee) Mariana Castanheira, PhD, AbbVie (formerly Allergan ) (Research Grant or Support)Bravos Biosciences (Research Grant or Support)Cidara Therapeutics, Inc. (Research Grant or Support)Cipla Therapeutics (Research Grant or Support)Cipla USA Inc. (Research Grant or Support)GlaxoSmithKline (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Melinta Therapeutics, LLC (Research Grant or Support)Pfizer, Inc. (Research Grant or Support)Qpex Biopharma (Research Grant or Support)Shionogi (Research Grant or Support)Spero Therapeutics (Research Grant or Support) Mariana Castanheira, PhD, Affinity Biosensors (Individual(s) Involved: Self): Research Grant or Support; Allergan (Individual(s) Involved: Self): Research Grant or Support; Amicrobe, Inc (Individual(s) Involved: Self): Research Grant or Support; Amplyx Pharma (Individual(s) Involved: Self): Research Grant or Support; Artugen Therapeutics USA, Inc. (Individual(s) Involved: Self): Research Grant or Support; Astellas (Individual(s) Involved: Self): Research Grant or Support; Basilea (Individual(s) Involved: Self): Research Grant or Support; Beth Israel Deaconess Medical Center (Individual(s) Involved: Self): Research Grant or Support; BIDMC (Individual(s) Involved: Self): Research Grant or Support; bioMerieux Inc. (Individual(s) Involved: Self): Research Grant or Support; BioVersys Ag (Individual(s) Involved: Self): Research Grant or Support; Bugworks (Individual(s) Involved: Self): Research Grant or Support; Cidara (Individual(s) Involved: Self): Research Grant or Support; Cipla (Individual(s) Involved: Self): Research Grant or Support; Contrafect (Individual(s) Involved: Self): Research Grant or Support; Cormedix (Individual(s) Involved: Self): Research Grant or Support; Crestone, Inc. (Individual(s) Involved: Self): Research Grant or Support; Curza (Individual(s) Involved: Self): Research Grant or Support; CXC7 (Individual(s) Involved: Self): Research Grant or Support; Entasis (Individual(s) Involved: Self): Research Grant or Support; Fedora Pharmaceutical (Individual(s) Involved: Self): Research Grant or Support; Fimbrion Therapeutics (Individual(s) Involved: Self): Research Grant or Support; Fox Chase (Individual(s) Involved: Self): Research Grant or Support; GlaxoSmithKline (Individual(s) Involved: Self): Research Grant or Support; Guardian Therapeutics (Individual(s) Involved: Self): Research Grant or Support; Hardy Diagnostics (Individual(s) Involved: Self): Research Grant or Support; IHMA (Individual(s) Involved: Self): Research Grant or Support; Janssen Research & Development (Individual(s) Involved: Self): Research Grant or Support; Johnson & Johnson (Individual(s) Involved: Self): Research Grant or Support; Kaleido Biosceinces (Individual(s) Involved: Self): Research Grant or Support; KBP Biosciences (Individual(s) Involved: Self): Research Grant or Support; Luminex (Individual(s) Involved: Self): Research Grant or Support; Matrivax (Individual(s) Involved: Self): Research Grant or Support; Mayo Clinic (Individual(s) Involved: Self): Research Grant or Support; Medpace (Individual(s) Involved: Self): Research Grant or Support; Meiji Seika Pharma Co., Ltd. (Individual(s) Involved: Self): Research Grant or Support; Melinta (Individual(s) Involved: Self): Research Grant or Support; Menarini (Individual(s) Involved: Self): Research Grant or Support; Merck (Individual(s) Involved: Self): Research Grant or Support; Meridian Bioscience Inc. (Individual(s) Involved: Self): Research Grant or Support; Micromyx (Individual(s) Involved: Self): Research Grant or Support; MicuRx (Individual(s) Involved: Self): Research Grant or Support; N8 Medical (Individual(s) Involved: Self): Research Grant or Support; Nabriva (Individual(s) Involved: Self): Research Grant or Support; National Institutes of Health (Individual(s) Involved: Self): Research Grant or Support; National University of Singapore (Individual(s) Involved: Self): Research Grant or Support; North Bristol NHS Trust (Individual(s) Involved: Self): Research Grant or Support; Novome Biotechnologies (Individual(s) Involved: Self): Research Grant or Support; Paratek (Individual(s) Involved: Self): Research Grant or Support; Pfizer (Individual(s) Involved: Self): Research Grant or Support; Prokaryotics Inc. (Individual(s) Involved: Self): Research Grant or Support; QPEX Biopharma (Individual(s) Involved: Self): Research Grant or Support; Rhode Island Hospital (Individual(s) Involved: Self): Research Grant or Support; RIHML (Individual(s) Involved: Self): Research Grant or Support; Roche (Individual(s) Involved: Self): Research Grant or Support; Roivant (Individual(s) Involved: Self): Research Grant or Support; Salvat (Individual(s) Involved: Self): Research Grant or Support; Scynexis (Individual(s) Involved: Self): Research Grant or Support; SeLux Diagnostics (Individual(s) Involved: Self): Research Grant or Support; Shionogi (Individual(s) Involved: Self): Research Grant or Support; Specific Diagnostics (Individual(s) Involved: Self): Research Grant or Support; Spero (Individual(s) Involved: Self): Research Grant or Support; SuperTrans Medical LT (Individual(s) Involved: Self): Research Grant or Support; T2 Biosystems (Individual(s) Involved: Self): Research Grant or Support; The University of Queensland (Individual(s) Involved: Self): Research Grant or Support; Thermo Fisher Scientific (Individual(s) Involved: Self): Research Grant or Support; Tufts Medical Center (Individual(s) Involved: Self): Research Grant or Support; Universite de Sherbrooke (Individual(s) Involved: Self): Research Grant or Support; University of Iowa (Individual(s) Involved: Self): Research Grant or Support; University of Iowa Hospitals and Clinics (Individual(s) Involved: Self): Research Grant or Support; University of Wisconsin (Individual(s) Involved: Self): Research Grant or Support; UNT System College of Pharmacy (Individual(s) Involved: Self): Research Grant or Support; URMC (Individual(s) Involved: Self): Research Grant or Support; UT Southwestern (Individual(s) Involved: Self): Research Grant or Support; VenatoRx (Individual(s) Involved: Self): Research Grant or Support; Viosera Therapeutics (Individual(s) Involved: Self): Research Grant or Support; Wayne State University (Individual(s) Involved: Self): Research Grant or Support